Increasing the Efficiency of Chebyshev Segment Fractional Rational Approximation - Vakal, L. P.; Kalenchuk-Porkhanova, A. A.; Vakal, E. S. (Cybernetics and systems analysis, 2017)
An algorithm for Chebyshev segment approximation with free nodes is presented. Fractional rational functions are used as approximating functions on subintervals. The differential evolution algorithm is used to find optimal nodes. Numerical results related to segment approximation of functions with optimal nodes are given.